Parakari a New Genus of the Family Baetidae (Insecta: Ephemeroptera) from Guyana Highlands - Nieto, Carolina; Derka, Tomáš (Zootaxa, 2011)
Baetidae is one of the most diverse families of Ephemeroptera. In South America this family now encompasses 27 genera and more than 130 species. The Guyana region is known for its extraordinary diversity and high level of endemism, which is, above all, remarkable at the tops of the isolated flat-topped table mountains – tepuis. Recently various international speleological expeditions to Churí-tepui explored the cave systems of this mountain. Here we describe a new genus of Baetidae recently found during the mentioned expeditions to Churí-tepui and Auyán-tepui. Parakari n. gen. can be distinguish from the other genera of this family, among other characters, in the nymphs by the absence of abdominal gills I, tarsal claws with subapical denticle larger than the others, right mandible with prostheca bifid and pectinate and with incisors positioned in obtuse angle to mola area, lingua with a tuft of setae, segment II of maxillary palpi with a concavity and a hole apically and segment II of labial palpi with a strong distomedial projection. In the adults the hind wings are absent and genitalia with segment II of forceps with a constriction, segment III elongate and long. Two new species are included in this genus; each one was collected at different tepui. A key and illustrations are included.